Tensiomyography, functional movement screen and counter movement jump for the assessment of injury risk in sport: A systematic review of original studies of diagnostic tests - Velarde-Sotres, Á.; Bores-Cerezal, A.; Alemany-Iturriaga, J.; Calleja-González, J. (Frontiers in Sports and Active Living, 2025)
Background: Scientific research should be carried out to prevent sports injuries. For this purpose, new assessment technologies must be used to analyze and identify the risk factors for injury. The main objective of this systematic review was to compile, synthesize and integrate international research published in different scientific databases on Countermovement Jump (CMJ), Functional Movement Screen (FMS) and Tensiomyography (TMG) tests and technologies for the assessment of injury risk in sport. This way, this review determines the current state of the knowledge about this topic and allows a better understanding of the existing problems, making easier the development of future lines of research.